" See and Treat" Approach is Appropriate in Women with High- grade Lesions on either Cervical Cytology or Colposcopy - Aue-Aungkul A. (2014)
This study was undertaken to evaluate the overtreatment rate of women with abnormal cervical cytology undergoing colposcopy followed by loop electrosurgical excision procedure (LEEP), the so-called " see and treat" approach. Overtreatment was defined as LEEP specimens containing cervical intraepithelial neoplasia (CIN) 1 or less. In this study, medical records of 192 women with abnormal Pap smears undergoing the " see and treat" approach in Chiang Mai University Hospital between October 2008 and October 2010 were reviewed. The preceding Pap smears were as follows: 124 (64.6%) with high-grade squamous intraepithelial lesion (HSIL); 35 (18.2%) with atypical squamous cells cannot exclude high-grade squamous intraepithelial lesion (ASC-H); 20 (10.4%) with low-grade squamous intraepithelial lesion (LSIL); 9 (4.7%) with squamous cell carcinoma (SCCA); and 4 (2.1%) with atypical squamous cells of undetermined significance (ASC-US). Histologic results obtained from loop electrosurgical excision procedure (LEEP) were as follows: CIN 2-3, 106 (55.2%); invasive cancer, 41 (21.4%); CIN 1, 15 (7.8%); adenocarcinoma in situ (AIS), 1 (0.5%); and no lesion, 29 (15.1%). Overall, 22.9% of LEEP specimens contained CIN 1 or less. Significant predictors for overtreatment were type of preceding smears and colposcopic impression. If the " see and treat" approach was strictly carried out in women who had either smears or colposcopic findings revealing high-grade disease, the overtreatment rate was only 7%. Hemorrhagic complication was 6.2% and all could be treated at an outpatient department. In conclusion, the overtreatment rate of the " see and treat" approach in women with various degree of abnormal Pap smears is 23% which would be diminished to the acceptable rate of lower that 10% if strictly performed in those with either smears or colposcopic impressions revealing high-grade abnormality. Peri-operative LEEP complications were mild and acceptable.